Boneka Geometri Smart Solusi Pengurangan Limbah Plastik Dan Belajar Matematika Menarik - Sindi Novelia (Jurnal Ilmiah Kanderang Tingang, 2023)
The problem of plastic waste in Indonesia is still an unresolved environmental problem. The high interest in using plastic by the community is one of the causes of the high plastic waste. Therefore, an initiative is needed to reduce plastic waste, one of which is the creative idea of ​​making a Smart Geometry Doll (BGS) product by utilizing plastic waste into something valuable and very useful. The purpose of this program is to analyze business opportunities through the manufacture of Geometry Smart Doll products as a solution for reducing plastic waste and learning interesting mathematics. The methods include: (1) Pre-production stage, this stage is carried out by procuring tools and materials, surveying raw materials, and leasing third-party services. (2) Production stage, at this stage plastic waste recycling, QR code and website creation, and doll sewing process (3) Marketing and promotion stage, BGS marketing is carried out online in the marketplace and offline at Muhammadiyah Elementary Schools in East Java. The results: (1) Smart geometry dolls that have flat-shaped characteristics, (2) QR codes and websites (3) Sales of BGS products from August to September were 34 dolls, with a profit of Rp. 455,600. Conclusion The Geometry Smart Doll product has a pretty promising selling power, and the results of the production have received quite an encouraging response from the public.